2001
DOI: 10.1111/j.1349-7006.2001.tb01185.x
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of the KAI1 Metastasis Suppressor Gene in Human Prostate Cancer Cell Lines

Abstract: Expression of the KAI1 gene, a metastasis-suppressor for prostate cancer, is reduced in all foci of prostatic metastasis. The altered regulatory mechanism is not strongly related to mutations or allelic losses of the KAI1 gene in prostate tumors. Since transcriptional silencing of genes has been found to be caused by epigenetic mechanisms, we have investigated the involvement of this epigenetic regulation of KAI1 expression in prostate cancers. The methylation status of the KAI1 promoter region was examined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 14 publications
(13 reference statements)
3
16
0
1
Order By: Relevance
“…In the present study, and NL9980 cells by bisulfite sequencing, while the MSP assay demonstrated non-methylation of KAI1 promoter in these two cell lines. There were reports from several groups suggested that methylation may not the key mechanism for reduction of KAI1 expression, which suggest that other pathway was involved in KAI1 regulation (21,37,38). Taken together, these result implicated that KAI1 was not methylated at least in cancer cell NL9980 or L9981.…”
Section: Discussionmentioning
confidence: 78%
“…In the present study, and NL9980 cells by bisulfite sequencing, while the MSP assay demonstrated non-methylation of KAI1 promoter in these two cell lines. There were reports from several groups suggested that methylation may not the key mechanism for reduction of KAI1 expression, which suggest that other pathway was involved in KAI1 regulation (21,37,38). Taken together, these result implicated that KAI1 was not methylated at least in cancer cell NL9980 or L9981.…”
Section: Discussionmentioning
confidence: 78%
“…Trainer and co-workers later showed that treatment of murine melanoma cells with the DNA de-methylating agent 5-azacytidine resulted in reversible reduction of metastatic lung colonization (43). Recent studies have shown that treatment of cells with 5-azacytidine can induce expression of the metastasis suppressor genes Nm23 (44) and KAI1 (45). Links between metastasis and HDAC activity first became apparent when the breast cancer metastasis promoting gene, MTA1, was identified as a component of the NuRD⅐HDAC complex (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…However, the underlying cause for loss of KAI1 expression in advanced tumours and tumour cell lines remains unknown. Available evidence suggests that mechanisms including loss of heterozygosity at the KAI1 locus on human chromosome 11p11.2, gene or promoter mutation and promoter hypermethylation are not responsible (Dong et al, 1996;Tagawa et al, 1999;Liu et al, 2000;Miyazaki et al, 2000;Sekita et al, 2001). Another possible explanation is that loss of KAI1 expression might reflect altered transcriptional regulation.…”
Section: Introductionmentioning
confidence: 99%